A regulaç\~ao das emiss\~oes de gases de efeito estufa no Brasil - Ronaldo Seroa da Motta (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper discusses the regulatory aspects of recent Brazilian commitments at COP 15 of the Climate Convention. Initially describes the evolution of regulatory instruments of the Convention, including the National Appropriate Mitigation Actions. Next the Brazilian sectoral mitigation targets and their funding opportunities, as financial incentives for low carbon activities or by creating a carbon market, are analyzed. This analysis is undertaken according to the regulatory framework of the recent National Policy on Climate Change (PNMC) that determines the country`s actions to combat climate change. In doing so, it addresses some regulatory issues still need to be developed for economic instruments as well as governance arrangements. Finally, it provides an overview of the political economy of the negotiations at COP 15 and points out possible paths for future coordination of global efforts to control greenhouse gases.
Keywords: Q54; 330; Klimawandel; Brasilien